Water and solar radiation productivity of double-crops in a humid temperate area - Van Opstal, Natalia Veronica; Caviglia, Octavio; Melchiori, Ricardo Jose (Southern Cross Publishing, 2020)
The intensification of agricultural systems including sequential double-crops provides a reliable platform to increase the water and solar radiation use in many humid temperate areas of South America, which are predominantly dominated by soybean as a sole crop. Our aim was to evaluate water and solar radiation productivity, as a measure of the whole system efficiency, in sole-crops and double-crops in a humid temperate area of Argentina (31.5º S, 60.3º W, 110 m.a.s.l). An experiment including spring wheat, flax, rapeseed, peas and soybean as sole-crops and the sequential combination of winter crops with soybean as a second crop was carried out during the 2007/08 cropping season. We measured soil water content and solar radiation interception in order to estimate crop evapotranspiration and total intercepted solar radiation as a measure of the total captured resource by crops. Water and radiation use efficiencies were calculated as a ratio between grain yield and the captured resource. Water and solar radiation productivity were calculated as the product of the proportion of annual offer (rainfall or incident solar radiation) of the resources captured by crops, i.e. the capture efficiency and the resource use efficiency to produce grain yield. Capture efficiency was higher in double-crops than in sole-crops (average 0.99 vs. 0.51 for water and 0.41 vs. 0.18 for solar radiation). In contrast, the averages of resource use efficiency recorded were similar in sole- and double-crops (average 0.85 g m-2 mm-1 for water and 0.58 g MJ-1 for solar radiation). Therefore, water and radiation productivity were associated mainly with resource capture. The inclusion of double-crops led to a more efficient use of the annual offer of resources as reflected by the increased water and radiation productivity in double-crops as compared with sole-crops. Therefore, double cropping appears as a feasible option to increase the whole system efficiency and to improve the return of crop residues as compared with the simplified systems based on soybean of South America.